2019
DOI: 10.1111/ene.13937
|View full text |Cite
|
Sign up to set email alerts
|

Axonal water fraction as marker of white matter injury in primary‐progressive multiple sclerosis: a longitudinal study

Abstract: Background and purpose Diffuse white matter (WM) injury is prominent in primary‐progressive multiple sclerosis (PP‐MS) pathology and is a potential biomarker of disease progression. Diffusion kurtosis imaging allows the quantification of non‐Gaussian water diffusion, providing metrics with high WM pathological specificity. The aim of this study was to characterize the pathological changes occurring in the normal‐appearing WM of patients with PP‐MS at baseline and at 1‐year follow‐up and to assess their impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…Over the last decades, the application of advanced neuroimaging techniques and new processing methods [1] has clarified that damage of specific white matter (WM) tracts contributes to different aspects of clinical disability in multiple sclerosis (MS) [2][3][4][5][6][7]. Amongst WM tracts, the corpus callosum (CC) is one of the preferential sites of clinically eloquent damage [4][5]8], since it is the target of both direct damage from focal lesions/diffuse neurodegenerative processes and indirect damage deriving from Wallerian degeneration of axons transected by hemispheric lesions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, the application of advanced neuroimaging techniques and new processing methods [1] has clarified that damage of specific white matter (WM) tracts contributes to different aspects of clinical disability in multiple sclerosis (MS) [2][3][4][5][6][7]. Amongst WM tracts, the corpus callosum (CC) is one of the preferential sites of clinically eloquent damage [4][5]8], since it is the target of both direct damage from focal lesions/diffuse neurodegenerative processes and indirect damage deriving from Wallerian degeneration of axons transected by hemispheric lesions [9].…”
Section: Introductionmentioning
confidence: 99%
“…To assess functional fiber integrity, we relied on V intra , which corresponds to the AWF, a dMRI parameter derived from the NODDI technique (Zhang et al, 2012). Intra‐axonal volume/water is negatively correlated to fiber damage (By et al, 2017; Margoni et al, 2019), but positively correlated to efficacious neuronal function (Genç et al, 2018). To obtain functional proof that tracked fiber bundles are indeed involved in the processing of nociceptive signals, we correlated V intra with the self‐reported levels of recent pain experiences (NTPIS, (Cook et al, 2013)).…”
Section: Discussionmentioning
confidence: 99%
“…Among the mesoscopic dMRI parameters extracted by our Bayesian approach, the best measure of functional fiber integrity turned out to be the V intra that corresponds to the axonal water fraction (AWF) of NODDI. Indeed, a reduction in V intra was the most sensitive measure of white matter damage in the cervical spinal cord (By, Xu, Box, Bagnato, & Smith, 2017) and supratentorial fiber tracts (Margoni et al, 2019) of patients suffering from multiple sclerosis. In contrast, increased intra‐neurite volume within the gray matter was associated with higher intelligence (Genç et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Enthusiastic readers are referred to previous publications on this topic. 66,67 WMTI has been applied in clinical studies of MS, [68][69][70][71] and these studies suggested that a decrease in AWF in the white matter correlates with clinical disability, presumably reflecting chronic axonal loss. In animal models, WMTI has been shown to be capable of distinguishing different tissue pathologies in demyelinating lesions and tracking their longitudinal courses.…”
Section: White Matter Tract Integritymentioning
confidence: 99%